2019
DOI: 10.1049/el.2018.6857
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of local B 1 field as dosimeter of RF heating for implant in MRI

Abstract: Radio frequency (RF) heating is a serious risk for a patient with an elongated implant during MRI scan. The conventional dosimeter of specific absorption rate (SAR) and the recently proposed B 1+rms may not accurately indicate the implant heating. The local B 1 field around the tip of a lead and its relationship with the RF heating were studied by numerical simulations. It was found that regardless of the route of the lead, the angle or position of placement, there was a strong linear correlation between the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The challenge of investigating DBS effects on the human brain using 3T fMRI is the potential risk of brain damage caused by the possible displacement, heating, or radiofrequency‐induced stimulation of the implanted DBS system. To ensure safety, our group recently investigated the displacement force, torque, and vibration of the stimulator during long‐duration 3T MRI scanning 24,25 . Results demonstrated that the hazardous effect in the worst case was 0.17N for displacement force, 8mN·m for torque, and 52.4m/s 2 for vibration 26 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge of investigating DBS effects on the human brain using 3T fMRI is the potential risk of brain damage caused by the possible displacement, heating, or radiofrequency‐induced stimulation of the implanted DBS system. To ensure safety, our group recently investigated the displacement force, torque, and vibration of the stimulator during long‐duration 3T MRI scanning 24,25 . Results demonstrated that the hazardous effect in the worst case was 0.17N for displacement force, 8mN·m for torque, and 52.4m/s 2 for vibration 26 .…”
Section: Methodsmentioning
confidence: 99%
“…To ensure safety, our group recently investigated the displacement force, torque, and vibration of the stimulator during long-duration 3T MRI scanning. 24,25 Results demonstrated that the hazardous effect in the worst case was 0.17N for displacement force, 8mNÁm for torque, and 52.4m/s 2 for vibration. 26 These values were only 46%, 36%, and 8% of the safety thresholds defined by the American Society for Testing and Materials 27,28 and thus met the safety requirements.…”
Section: Mri Safetymentioning
confidence: 99%
“…However, this technique required hardware redesign of IMDs, and may introduce additional artifacts during MRI. Additionally, some studies reported the use of B1 (RF field) mapping methods [37][38][39][40] and the MRI-based determination of the transfer function (TF) of implants 41 , primarily measuring RF-induced currents in the conductive leads. Nevertheless, B1 and TF methods do not directly quantify the IMDs heating and require additional calibration or modelling.…”
Section: Discussionmentioning
confidence: 99%
“…A neurostimulator (G106R; Beijing PINS Medical Co., Ltd.) was also connected to the leads (model E202C; Beijing PINS Medical Co., Ltd.). This DBS system is reportedly safe for long-duration 3 T MRI [14][15][16]. Postoperative MRI was performed to confirm the location of the leads and identify signs of cerebral hemorrhage after surgery (Fig.…”
Section: Surgery and Stimulationmentioning
confidence: 99%